LAW 14.016 / 2020 AS AN INSTRUMENT TO FIGHT HUNGER AND PARTIAL CONCRETION OF THE RIGHT TO FOOD (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The presente article has as objective to demonstre the importance of the promulgation of Law 14.016 of June 23,2020, which provides for combating food waste and the donation of food excess for human consumption, because from there, countless establishments dedicated to the production and supply of food will not discard clean leftovers to deliver directly or indirectly to people and low-income families facing hunger. Thus, based on a hypothetical deductive analysis, it is shown that such a norm could be an instrument to fight hunger and partially concretize the right to food provided for in article 6 of the Federal Constitution, by satisfying the hunger of thousands of Brazilians with food consumption conditions.